1990
DOI: 10.1182/blood.v76.8.1464.1464
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of therapy for acute graft-versus-host disease: initial treatment

Abstract: We have reviewed results of therapy in 740 patients with grades II-IV acute graft-versus-host disease (GVHD) after allogeneic marrow transplantation. At the beginning of therapy, 597 patients (81%) had rash, 369 (50%) had liver dysfunction and 396 (54%) had gut dysfunction. Initial treatment was with glucocorticoids (n = 531), cyclosporine (n = 170), antithymocyte globulin (ATG) (n = 156) or monoclonal antibody (n = 3) either singly (n = 633) or in combination (n = 107). Parameters of GVHD severity in each org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
2
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(133 citation statements)
references
References 0 publications
4
119
2
8
Order By: Relevance
“…In a retrospective, 5-year survival in those patients response to steroid was significantly higher than those non-response to steroid (51% versus 32%). Similar result was also reported by Martin et al [84,85]. Unfortunately, onlỹ 60% of acute GVHD patients respond to systemic steroids and many of these responses are not durable [82,86,87].…”
Section: First-line Therapysupporting
confidence: 84%
“…In a retrospective, 5-year survival in those patients response to steroid was significantly higher than those non-response to steroid (51% versus 32%). Similar result was also reported by Martin et al [84,85]. Unfortunately, onlỹ 60% of acute GVHD patients respond to systemic steroids and many of these responses are not durable [82,86,87].…”
Section: First-line Therapysupporting
confidence: 84%
“…Their effect is likely to be due to lympholytic effects and anti-inflammatory properties (Deeg, 2007). Two early studies assessed response to corticosteroids in patients with grade II-IV GvHD (Martin et al, 1990;Weisdorf et al, 1990). Martin et al (1990) reported overall complete or partial responses in 44% of patients.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Two early studies assessed response to corticosteroids in patients with grade II-IV GvHD (Martin et al, 1990;Weisdorf et al, 1990). Martin et al (1990) reported overall complete or partial responses in 44% of patients. Improvement rates were 43% for skin disease, 35% for evaluable liver disease and 50% for evaluable gut disease.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Moreover, the current survival at years in patients who respond to steroids is about 36% versus 17% in nonresponders (NR) [6] and it has been shown that transplantation-related mortality (TRM) is higher in steroidresistant patients [7,8].…”
Section: Introductionmentioning
confidence: 99%